Reactive astrocytes and therapeutic potential in focal ischemic stroke - Choudhury, Gourav Roy (Neurobiol Dis, 2015)
Astrocytes are specialized and the most abundant cell type in the central nervous system (CNS). They play important roles in the physiology of the brain. Astrocytes are also critically involved in many CNS disorders including focal ischemic stroke, the leading cause of brain injury and death in patients. One of the prominent pathological features of a focal ischemic stroke is reactive astrogliosis and glial scar formation. Reactive astrogliosis is accompanied with changes in morphology, proliferation and gene expression in the reactive astrocytes. This study provides an overview of the most recent advances in astrocytic Ca(2+) signaling, spatial and temporal dynamics of the morphology and proliferation of reactive astrocytes as well as signaling pathways involved in the reactive astrogliosis after ischemic stroke based on results from experimental studies performed in various animal models. This review also discusses the therapeutic potential of reactive astrocytes in a focal ischemic stroke. As reactive astrocytes exhibit high plasticity, we suggest that modulation of local reactive astrocytes is a promising strategy for cell-based stroke therapy.